Peak Loads and Efficient Pricing - Steiner, Peter O. (Quarterly Journal of Economics, 1957)
Introduction, 585. — I. Solution of the two period peak load problem under simplifying assumptions, 587. — II. Relation of the solution to some earlier contributions, 592. — III. Can purely cost-based prices be used to achieve optimal results?, 596. — IV. Some policy implications, 602. — Mathematical Appendix, 604.